First-line nivolumab plus ipilimumab for unresectable MPM in China: a cost-effectiveness analysis - Liu Yang; Xiaobing Song; Wanxian Zeng; Zhiwei Zheng; Wenqiang Lin (Orphanet Journal of Rare Diseases, 2023)
Abstract Background The regimen of nivolumab plus ipilimumab (NI) has been recommended by the National Comprehensive Cancer Network Clinical Practice Guidelines in Oncology-Malignant Pleural Mesothelioma (Version 1.2022) and Chinese Guidelines for the Clinical Diagnosis and Treatment of Malignant Pleural Mesothelioma (2021 edition) as the first-line treatment for Malignant Pleural Mesothelioma (MPM). But whether immunotherapy has a financial advantage over conventional chemotherapy (pemetrexed plus cisplatin/carboplatin, C) is uncertain. Methods Based on survival and safety data from the CheckMate 743 clinical trial (NCT02899299), a partitioned survival model was constructed using TreeAge Pro2022 software. The model cycle was set to 1 month and the study period was 10 years. The output indicators included total cost, quality-adjusted life year (QALY) and incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were used to assess the robustness of the results, considering only direct medical costs. Results and discussion The ICER for group NI versus Group C was $375,656/QALY in all randomized patients, $327,943/QALY in patients with epithelioid histology, and $115,495/QALY in patients with non-epithelioid histology. The ICERs of all three different populations all exceeded the willingness-to-pay threshold (three times the per capita gross domestic product of China in 2021). The results of univariate sensitivity analysis showed that the price of pemetrexed and nivolumab had great influence on the analysis results. The results of the probabilistic sensitivity analysis show that the probability of the NI scheme being more economical in all three different populations was 0. What is new and conclusion From the perspective of the Chinese healthcare system, in patients with unresectable MPM, NI has no economic advantage over C.